Image encryption method based on multiple-order fractional discrete Tchebichef transform and generating sequence - Bin XIAO; Wenming SHI; Weisheng LI; Jianfeng MA (Tongxin xuebao)
Fractional transform based image encryption methods have been widely studied in recent years.However,most of the existing fractional transform based image encryption methods are defined in the complex field.Thus,the encrypted images contain both phase and amplitude information,which is not conducive to transmission and storage.Moreover,some encryption methods that meet the requirements of reality-preserving have problems of relatively single keys,lacking of sensitivity and so on.An image encryption method was proposed based on multiple-order fractional discrete Tchebichef transform and generating sequence.The proposed method used randomly generated row and column vectors and generating sequence generated by Chaotic sequences as keys to encrypt images,which not only satisfied property of reality-preserving transmission but also greatly expanded the key space.The experimental results further demonstrate that the proposed encryption method can resist a variety of attacks,and decrypted images are almost non-distored,which indicate excellent encryption effect,sufficient security and robustness of the method.